Edukasi Dan Implementasi Terapi Autogenik Untuk Penurunan Tingkat Kecemasan Pada Pasien Pre Sectio Caesarea - Nuranggreni, Maricha; Novitasari, Dwi; Yudha, Magenda Bisma (Yayasan Inspirasi El Burhani, 2024)
Introduction:. Anxiety is a frequent psychological reaction in patients before surgery. Patients should psychologically prepare for the operation since they will likely be afraid of needles, the pain that will accompany the incisions, the anaesthesia, and the potential complications that might arise, such as permanent impairment or even death. Objective: Efforts to improve the knowledge and skills of preoperative sectio caesarea patients about autogenic therapy techniques to reduce anxiety at the Banjarnegara Islamic Hospital. Method: Methods carried out Identifying the anxiety scale of activity participants before autogenic therapy using the APAIS anxiety measuring instrument, identifying the level of knowledge of participants before education related to autogenic therapy by filling out a questionnaire. provide education related to autogeni Result: After being given education, the majority of participants' knowledge level was in the high knowledge category of 20 participants (87%). Community Service participants education and implementation of autogenic therapy through audio visual media at Banjarnegara Islamic Hospital showed that before implementation, the majority of participants' anxiety was in the category of severe anxiety as many as 13 participants (56.5%) While after the implementation was given, the majority of participants' anxiety category was in the mild anxiety category as many as 13 participants (56.5%). Conclusion: The findings of this activity show that patients' anxiety levels go down after receiving autogenic treatment and their knowledge goes up after receiving instruction.